2020
DOI: 10.12697/jeful.2019.10.2.06
|View full text |Cite
|
Sign up to set email alerts
|

To agree or not to agree? English adjectives in Estonian-English bilingual blogs and vlogs

Abstract: The article focuses on the agreement (in case and number) of English adjectives used with Estonian nouns in noun phrases (Eng ADJ + EST N) in Estonian blogs and vlogs. According to the Matrix Language Frame model (MLF), one would expect English adjective stems to take on Estonian inflections, but this is not always the case. The data comes from fashion and lifestyle blogs and vlogs that have Estonian as the main language and contain English language material to various degrees. Altogether, 84 noun phrases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Figure 3 demonstrates this pattern with a reference to one specific adjective type: disyllabic adjectives ending with [i] (fancy) in the agreement condition. In the study by Kask (2019) this was the type that always agreed with the noun in number and case, however, among our participants its perception exhibited variation. As "Category and Acceptability Rates" and "Adjective Type and Acceptability Rates" sections demonstrate, the acceptability rate is higher among participants with higher proficiency in and exposure to English.…”
Section: What Can(not) Be Explained By Sociodemographics and Structural Compatibilitymentioning
confidence: 43%
See 4 more Smart Citations
“…Figure 3 demonstrates this pattern with a reference to one specific adjective type: disyllabic adjectives ending with [i] (fancy) in the agreement condition. In the study by Kask (2019) this was the type that always agreed with the noun in number and case, however, among our participants its perception exhibited variation. As "Category and Acceptability Rates" and "Adjective Type and Acceptability Rates" sections demonstrate, the acceptability rate is higher among participants with higher proficiency in and exposure to English.…”
Section: What Can(not) Be Explained By Sociodemographics and Structural Compatibilitymentioning
confidence: 43%
“…Based on that, it would be expected that in a bilingual phrase English adjectives would agree with Estonian nouns, at least in the event when an English adjective is compatible with Estonian adjective declensions. A study by Kask ( 2019 ) showed that in bilingual blogs and vlogs the English adjective does not agree with the noun if it does not fit into the Estonian declension system. There is a tendency for agreement, if English adjectives are phonotactically similar to Estonian adjectives and, therefore, are structurally compatible with the declension system.…”
Section: Adjectives In Bilingual Phrase English Adj + Estonian Nmentioning
confidence: 99%
See 3 more Smart Citations